DIGITAL MARKETING ANALYSIS SME: A CASE STUDY IN PUSAT PENGEMBANGAN KEWIRAUSAHAAN LPPM UNIVERSITAS SAM RATULANGI - Mongkau, Nikita E.M; Massie, James D. D.; Tumbuan, Willem J.F.A (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: A lot of enterprises has to implement the internet for their business, especially for small-medium enterprise (SME’s) they should use the internet for developing their business. Digital marketing is a powerful strategy to grow up the business and strengthen the brand awareness. This research aims to examine the implementation of digital marketing and analysis the effectiveness young enterprises toward using social media as digital tools to build brand awareness. All of the respondents are from Pusat Penegembangan Kewirausahaan LPPM Universitas Sam Ratulangi as a sample of young enterprises. The result have shown that digital marketing become main purpose while implement this strategy, however there is still gap between customer who are buying through online and offline, also still of lack in feedback from the customer is a main problem. The recommendations for this research are in terms of digital marketing with social media, young enterprise should create social media accounts for businesses that are separate from personal accounts, make account names simple, easy to remember, explain their business, and have the same name as other social media platforms used and also for the sme’s that want to use the digital marketing strategy they can consider to use the strategy. Keywords: digital marketing, social media marketing, small-medium enterprises.